An empirical inquiry into the antecedents and consequences of perceived e-retailer's resilience. (2018) - Raju, G. Amar; Roy, Souvik; Mandal, Santanu
Resilience has been an important dynamic capability for manufacturers and service providers. The study extends the notion of resilience from manufacturing to e-retailer. The study contends that e-retailers need resilience to sustain their operations in event of IT or technological failure. Our study conceptualised perceived resilience construct for e-retailer and explored its antecedents and consequents. Partial least squares (PLS) was used as the statistical tool for testing the proposed hypotheses in this study. Based on 309 completed responses, our study undersigned perceived information quality and perceived system quality as dominant enablers of perceived e-retailer's resilience. Further, perceived e-retailer's resilience was found to positively influence customer satisfaction and engagement; both of them in turn enhance customer loyalty. The study is the foremost to develop e-retailer's resilience construct and with empirical validation. Further, the study also developed a comprehensive model for perceived e-retailer's resilience based on its enablers and outcomes. Implications for business firm's managers and practitioners are also provided.